Dukungan Sosial terhadap Kualitas Hidup Pasien Kanker - Arif Rahman; Dewi Gayatri; Agung Waluyo (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the effectiveness of social support on the quality of life of cancer patients. The method used is a systematic review with literature searches using databases such as PROQUEST, Scopus, EBSCOhost, ClinicalKey Nursing, and other search sources. The article selection process uses the PRISMA method. The number of articles found in the initial search was 5,955. Seventeen papers were selected based on the title and abstract. Reports were read in total, and only 12 articles were used in this review, according to the selected criteria. The research results show that social support positively influences the patient's quality of life. Keywords: Social Support, Cancer, Quality of Life